Diseño De Una Herramienta Para La calibración De válvulas Limitadoras De presión Primarias En Palas Hidráulicas Komatsu En La Empresa El Cerrejón En La Guajira (2022)
The present project is focused on the remote maintenance of the PC4000 hydraulic shovels of the Komatsu company, based on the safety of the operator or technician who performs the maintenance of the shovels, for which it has been proposed to carry out a design that complies with this requirement for this objective to be achieved, also this tool will help the technicians for performing the calibration of the valves not to be directly subjected to taking risks in their apparatus due to high pressures that are handled, also exposing their health and life, since that the pressures that are handled are extremely high and an error in the calculations can be fatal